Gene silencing of human neuronal cells for drug addiction therapy using anisotropic nanocrystals - Mahajan, Supriya D. (2013)
Theranostic platform integrating diagnostic imaging and therapeutic function into a single system has become a new direction of nanoparticle research. In the process of treatment, therapeutic efficacy is monitored. The use of theranostic nanoparticle can add an additional "layer" to keep track on the therapeutic agent such as the pharmacokinetics and biodistribution. In this report, we have developed quantum rod (QR) based formulations for the delivery of small interfering RNAs (siRNAs) to human neuronal cells. PEGlyated QRs with different surface functional groups (amine and maleimide) were designed for selectively down-regulating the dopaminergic signaling pathway which is associated with the drug abuse behavior. We have demonstrated that the DARPP-32 siRNAs were successfully delivered to dopaminergic neuronal (DAN) cells which led to drastic knockdown of specific gene expression by both the electrostatic and covalent bond conjugation regimes. The PEGlyated surface offered high biocompatibilities and negligible cytotoxicities to the QR formulations that may facilitate the in vivo applications of these nanoparticles.